Exploring the Intersection of Psychological Features and Language Proficiency in Seamen's Activity: A Qualitative Analysis of Maritime Cadets at Maritime Institute Jakarta (STIP Jakarta) - Marudut Bernadtua Simanjuntak (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This research delves into the psychological features of seamen's activity during emergency situations as perceived by 240 cadets in their third semester at the Maritime Institute Jakarta (STIP Jakarta). The study employs a qualitative descriptive approach to unravel the cognitive, emotional, and behavioural responses exhibited by cadets in simulated emergency scenarios. The findings underscore the transformative journey of cadets, transitioning from initial stress and anxiety to a controlled sense of urgency, showcasing the efficacy of the institution's training methodologies. A significant aspect of this research is the examination of the correlation between language proficiency, particularly in English, and effective emergency communication. Cadets recognise English as a shared language that enhances communication efficiency during emergencies. The study reveals the pivotal role of linguistic skills in coordinating actions seamlessly, highlighting the practical implications of language proficiency in emergency management within the global maritime context. The implications for maritime education are profound, emphasising the need for a holistic approach that integrates psychological preparedness and targeted language development initiatives. The research recommends continuous professional development, global collaboration among maritime institutions, and industry partnerships to ensure the adaptability and relevance of education to evolving industry standards. In conclusion, this research contributes valuable insights to the discourse on maritime education, emphasising the importance of cultivating a well-rounded skill set among cadets. The findings inform curriculum development, training methodologies, and strategies to enhance the psychological resilience and linguistic proficiency of future seafaring professionals, positioning them as adept and globally competent officers.